2016
DOI: 10.1007/s11427-016-5059-9
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular characteristics of the ompA gene of serotype B Chlamydia trachomatis in Qinghai Tibetan primary school students

Abstract: To study the molecular characteristics of Chlamydia trachomatis, the major outer membrane protein gene (ompA) of C. trachomatis from primary school students with trachoma residing in the Qinghai Tibetan area was sequenced and compared with the same serotype in GenBank. In Jianshetang Primary School and Galeng Central Primary School in the Galeng Tibetan Township of Qinghai Haidong Sala Autonomous County, scraped samples were collected from the upper tarsal conjunctiva and lower conjunctival sac of both eyes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…A total of 115 trachoma swabs from each conjunctiva with one or more follicles and the corresponding conjunctival sac were collected. All samples were examined using a commercial qPCR kit detecting chlamydial plasmid and ompA sequencing for qPCR-positive conjunctiva swabs was performed, as previously described (Li et al, 2016; Wang N. et al, 2016). Forty-five swabs from 26 students were qPCR-positive for C. trachomatis infection and two type-B ompA variants were identified.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 115 trachoma swabs from each conjunctiva with one or more follicles and the corresponding conjunctival sac were collected. All samples were examined using a commercial qPCR kit detecting chlamydial plasmid and ompA sequencing for qPCR-positive conjunctiva swabs was performed, as previously described (Li et al, 2016; Wang N. et al, 2016). Forty-five swabs from 26 students were qPCR-positive for C. trachomatis infection and two type-B ompA variants were identified.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al previously reported the identification of two type-B ompA variants in 37 qPCR-positive conjunctival samples (Li et al, 2016). Here, we report the finding of another ompA variant in a single sample of no.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations